Pengaruh Program Bauran Pemasaran Jasa Terhadap Perolehan Laba Perusahaan Jasa Konsultan Perencana Bangunan - Surachman Surjaatmadja (Universitas Kristen Maranatha, 2005)
The turbulence environment affects the customer requirements of the needs and wants of product or service. Competition in the industry is becoming very keen. To win this competition company needs implementative and adaptive marketing programme and strategy to deliver the product or service, so that the customer accepts it better than the competitors (superior). Marketing mix programme which have been selected from the market informations. This research aims : To know and analysis the influence of service marketing mix programme toward the Performance of Consultant Firms. In this research is used the Strategic Marketing Management Approach, especially evaluated from internal strategy of the firm that is Service Marketing Mix Programs toward the Performance of the Firms. The characters of this research is verificative and descriptive, while research methode is survey explanatory, by using the sampling technique of simple random sampling to 140 Consultant Planner of Building Firms. The results of this research indicate that service marketing mix programme have an associated relationship to firm performance R2X1 directly each for Product 14.40%, Price 17.0%, Promotion is 32.0%, Distribution is 26.0% Physical evidence 58.0%1, Personnel 20.0% and Process is 20.0% totally is 97.60%.